2018
DOI: 10.1080/20018525.2018.1447221
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant status, iron homeostasis, and carotenoid levels of COPD patients with advanced disease and LTOT

Abstract: Background: The pathogenesis of chronic obstructive pulmonary disease (COPD) is associated with oxidative stress. Both iron (Fe) and oxygen are involved in the chemical reactions that lead to increased formation of reactive oxygen species. Oxidative reactions are prevented by antioxidants such as carotenoids. Objective: To study the differences in Fe status, carotenoid levels, healthy eating habits, and markers of inflammation and oxidative damage on proteins in subjects with severe COPD ± long-term oxygen the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The combined prevalence of all types of ID detected in this study was 30%, the most frequent type being CID. A few studies exploring the possible causality between COPD pathogenesis and severity to ID and/or anemia have already been published [21][22][23][24][25][26][27], but the comparison of ID frequencies is difficult as definitions vary across the available literature. Nickol et al were the first ones to investigate ID using definitions targeting absolute ID and identifying 18% to be iron-deficient [21], which is distinctly more than 9.3% of AID in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The combined prevalence of all types of ID detected in this study was 30%, the most frequent type being CID. A few studies exploring the possible causality between COPD pathogenesis and severity to ID and/or anemia have already been published [21][22][23][24][25][26][27], but the comparison of ID frequencies is difficult as definitions vary across the available literature. Nickol et al were the first ones to investigate ID using definitions targeting absolute ID and identifying 18% to be iron-deficient [21], which is distinctly more than 9.3% of AID in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, an imbalance between an excess of oxidants and insufficient antioxidant resources, appears to trigger a number of inflammatory, obstructive, and fibrotic lung disorders and contributes to the development of COPD (15). This imbalance is known to play an important role in the pathogenesis of the disease through direct injurious effects, and by involvement in the molecular mechanisms that control lung inflammation (16).…”
Section: Chapter Onementioning
confidence: 99%
“…Reactive oxygen species (ROS), such as superoxide anion, hydrogen peroxide, and hydroxyl radicals (17), are generated by inflammatory cells in the lung in response to different stimuli, including tobacco smoke (15). Past studies have found that large numbers of neutrophils and macrophages in the lungs of COPD patients generate ROS in excess such that these patients have higher levels of superoxide anion and hydrogen peroxide release (17).…”
Section: Chapter Onementioning
confidence: 99%
See 2 more Smart Citations